A study of electromagnetic free forming in AA5052 using digital image correlation method and FE analysis. (January 2019) - Deng, Huakun; Mao, Yunfei; Li, Guangyao; Cui, Junjia
Graphical abstract: Highlights A new experiment setup which combines DIC technique was applied to study the high-rate deformation behavior of aluminum sheet. A FEA/BEM numerical model was established and had good consistency with the EMF experiments. Maximum strain rate was observed at the dome apex at the end of the deformation due to the velocity concentration caused by inertia effect. Experimental and numerical results confirmed that different strain histories would affect material behaviors of formed parts. Abstract: Electromagnetic forming (EMF) is a promising process that can improve the forming limit under room temperature. In this work, AA5052 sheets were electromagnetic free formed at various discharging energies with an elliptic spiral coil and an elliptical hollow die. Two high-speed cameras with a certain angle to each other photographed the entire deformation process. Full-field displacement, velocity, strain and strain rate were calculated by a digital image correlation (DIC) system. The sheets were deformed into oval domes and the peak strain rate measured was about 12, 400 s - 1 . A 3D numerical model was established using the method of combing Finite Analysis (FEA) and Boundary Element Method (BEM). The simulation results were in good agreement with the experiments. Sheet deformation at the center region had a significant delay relative to the periphery region, and the velocity curves could be divided into three stages: initial increase, speed sustention and second-time increase. Several microscopic test regions with same final equivalent strain but different strain histories were confirmed by DIC technology and FEA/BEM model. Different strain histories would affect grain distribution and local hardness.